Death Beliefs and Rituals Among The Kınık Chepni in Arpaseki Village: An EvaluationiIn Terms of Mythic Background and Ancient Turkic Beliefs (Journal of Alevism-Bektashism Studies, 2025)
This study examines the beliefs surrounding death and the rituals structured around it among the Chepni community living in Arpaseki Village, located in the Kınık district of İzmir, through a fieldwork-based methodological approach. The research focuses on the mythological background of these practices and their enduring connections with ancient Turkic belief systems. Although these rituals are outwardly performed within an Islamic and Alevi-Bektashi framework, the study is grounded in the central argument that their deep structural layers distinctly preserve pre-Islamic Turkic cultural and religious codes, most notably those associated with Shamanism. The data of the study were obtained through interviews conducted with 31 informants as part of an extensive field study carried out in the village. The collected material was classified and analyzed under three main categories: beliefs and practices preceding death, funeral preparations and burial processes, and post-mortem mourning and commemorative practices. The findings reveal that among the Arpaseki Chepni, death is not perceived as an “end” but rather as a transition of the soul to another plane of existence, marking a new beginning. Omens preceding death—such as dreams, animal behavior, and physical changes; burial practices including the construction of a symbolic “dwelling” in the grave, covering the grave with pine branches after burial, and lighting kindling at the place where the deceased is washed; as well as strict observances during the forty-day mourning period and the Dardan İndirme ritual specific to the Alevi-Bektashi tradition—all constitute manifestations of continuity with the ancient Turkic Sky God belief, the ancestor cult, nature cults, and Shamanistic cosmology. This article argues that, in the specific case of Arpaseki Village, Chepni culture uniquely synthesizes the ancient Turkic mythological worldview with Islamic and Alevi-Bektashi beliefs. This synthesis becomes particularly visible in practices centered on death and offers valuable insights into the historical depth, transformation, and continuity of Turkic culture.